2020
DOI: 10.1002/lno.11462
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing ventilation events in an anoxic coastal basin: Observed dynamics and the role of climatic drivers

Abstract: Restricted horizontal exchange and vertical stratification restrict ventilation of bottom waters in many coastal systems, leading to stagnant basin water conditions. Dense inflows from oceanic sources can lead to dramatic changes in basin-scale properties over very short timescales. Here, we used a semi-enclosed coastal basin with deep-anoxia (Lough Furnace) as a test bed, in order to discern estuary-ocean exchange dynamics that lead to irregular and ephemeral deep-water ventilations. Measured densities and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
(119 reference statements)
0
3
0
Order By: Relevance
“…If water supplied by mixing or advection is relatively poor in viable nitrifier biomass but contains ammonium or organic N, ammonium and nitrite may consequently accumulate due to delayed nitrification and associated temporal decoupling of nitrification. This could apply to subsurface waters of seasonally mixed lakes where climatic variations can affect the extent of spring mixing (53) as well as fjord-like basins and estuaries similar to BB with seasonal stratification-mixing cycles and/or irregular intrusion events (22,35,54). The mechanism might even operate in shelf ecosystems subject to seasonal blooms and sinking of organic matter, periodic upwelling, or seasonal changes in shelfslope exchange (15,55,56).…”
Section: Control By Physical Mixing Explains Seasonal Changes In Ao Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…If water supplied by mixing or advection is relatively poor in viable nitrifier biomass but contains ammonium or organic N, ammonium and nitrite may consequently accumulate due to delayed nitrification and associated temporal decoupling of nitrification. This could apply to subsurface waters of seasonally mixed lakes where climatic variations can affect the extent of spring mixing (53) as well as fjord-like basins and estuaries similar to BB with seasonal stratification-mixing cycles and/or irregular intrusion events (22,35,54). The mechanism might even operate in shelf ecosystems subject to seasonal blooms and sinking of organic matter, periodic upwelling, or seasonal changes in shelfslope exchange (15,55,56).…”
Section: Control By Physical Mixing Explains Seasonal Changes In Ao Ratesmentioning
confidence: 99%
“…Moreover, all these effects are linked to weather and climate, since atmospheric forcing plays an important role for stratificationmixing patterns of ocean waters (61). For example, infrequent deep water renewal events in a coastal basin have been linked to variations in freshwater run-off and other atmospherically controlled variables (54). In BB, winter mixing is largely driven by heat loss to the atmosphere (32,39).…”
Section: Control By Physical Mixing Explains Seasonal Changes In Ao Ratesmentioning
confidence: 99%
“…Studies in lakes, coastal seas, and the ocean have shown that vertical mixing is often confined to the turbulent bottom boundary layers (Ledwell & Hickey, 1995; P. L. Holtermann et al., 2012) and may exhibit a strong seasonal variability (Axell, 1998; P. Holtermann & Umlauf, 2012; Williams et al., 2022). Often both large‐scale advective (e.g., Kelly et al., 2020; P. Holtermann et al., 2020) and small‐scale turbulent vertical transport (Rovelli et al., 2016) contribute to the total oxygen transport.…”
Section: Introductionmentioning
confidence: 99%